Obsessive - compulsive disorder - course during pregnancy, exacerbation factors - literature review - Czarnota, Julia; Cichoń, Katarzyna; Chyćko, Małgorzata; Kromer, Agata; Zapała, Magdalena Alicja; Gawryś, Agnieszka; Środoń, Agnieszka; Łapaj, Monika; Wilk, Joanna; Cholewa, Małgorzata Maria (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work: The period of pregnancy and puerperium is the time of increased vulnerability for mother’s mental deterioration. While disorders such as perinatal depression have been detailed, an impact of pregnancy on the course of other mental disorders such as OCD is less investigated. The purpose of this work was to draw attention to the factors that may influence exacerbation of obsessions and compulsions in pregnancy and during the postpartum period. The most common obsessions and compulsions of pregnant women and the influence of mother’s OCD on the newborn have also been described in this research. State of knowledge: Factors such as mother’s age, duration of pregnancy, method of delivery may be predictors of aggravation of obsessions and compulsions. Gestational diabetes, thyroid hormones levels, personality disorders of the mother, stress, cultural beliefs also have an impact on mother’s OCD. Infant being infected or hurt are the most common obsession subjects while cleaning and checking the baby happen to be the most frequent compulsions. Summary: It is important to disseminate knowledge about the course of OCD during pregnancy and postpartum period and pay attention to the inflammatory factors for earlier diagnosis and treatment. More research about factors worsening OCD through pregnancy are needed to be conducted.